Halal Awareness, Halal Certification, and Their Impact on Consumer Purchase Intention in Indonesia - Anjassyafara, Risyaldi Candra; El-Junusi, Rahman (Halal Science, 2025)
The rapid growth of the halal industry has increased the need for reliable halal products, yet concerns persist regarding consumer awareness and the credibility of certification systems. This study examines the effects of Halal Awareness and Halal Certification on Purchase Intention among university students in Semarang, Indonesia. A quantitative cross-sectional survey was conducted using structured online questionnaires distributed to 100 undergraduate students. This sample size meets minimum methodological recommendations for regression analyses, allowing adequate statistical testing of the proposed relationships. Data were analyzed through validity and reliability assessments, classical assumption tests, and multiple regression analysis using IBM SPSS Statistics 25. The results show that Halal Awareness (β = 0.391, p = 0.006) and Halal Certification (β = 0.566, p < 0.001) both have significant positive effects on Purchase Intention. The model explains 43.8% of the variance in purchase intention (Adjusted R² = 0.438), indicating moderate explanatory power while suggesting that more than half of consumer intention is influenced by factors not measured in this study. The analysis focuses specifically on awareness and certification constructs, without incorporating additional variables such as religiosity, perceived quality, or prior purchasing experience.Because the respondents were drawn from a single Islamic university, the findings are context-specific and not representative of the broader Indonesian population. Nonetheless, the study highlights the importance of improving consumer understanding of halal principles and strengthening certification credibility. Future research should employ more diverse samples and longitudinal designs to enhance generalizability and clarify causal relationships.